The Cross-Bar Technique for Pectus Excavatum Repair: A Key Element for Remodeling of the Entire Chest Wall - Hyun, Kwanyong; Park, Hyung Joo (European Journal of Pediatric Surgery, 2022)
Introduction The multiple bar approach was developed to cover broader and heavier teenager/adult chest wall deformities. We designed the cross-bar technique to achieve remodeling of the entire chest wall. This study aimed to demonstrate the role of cross-bar and its benefits over the parallel bar.Materials and Methods The cross-bar technique involves placing two bars diagonally and then cross on the target. The primary purposes are to double the lifting forces by making two bars converge on a single target to lift inflexible heavy chest wall depressions or cover lower lateral areas. The results of the cross-bar and parallel bar are compared for the indications, postrepair outcomes, and complications.Results From 2016 to 2019, 247 patients who underwent multiple bar pectus excavatum (PE) repair were enrolled in the study: 157 with cross-bar and 90 with parallel bar. In the cross-bar group, 33% (51/157) received three bars in XI fashion to cover the upper depression. The cross-bar group was older (18.0 ± 6.1 vs. 15.7 ± 5.0), had higher depression index (1.9 ± 0.7 vs. 1.8 ± 0.3), and was less asymmetric (45% vs. 71%) than those in the parallel bar group. The overall complication rates were not different between the two groups (9.6% vs. 10%, p = 1.0), although the cross-bar group was more rigid and complex. There was no bar displacement or reoperation in both groups.Conclusion The cross-bar technique is as safe and effective as the parallel-bar technique, even though it was selected to correct more complexities. The cross-bar technique could be a method for complex PE deformities for remodeling of the entire chest wall.
Keywords: pectus excavatum; minimally invasive repair; cross-bar technique; parallel-bar technique